2015
DOI: 10.14283/jpad.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Treatment Development for Neuropsychiatric Symptoms in Alzheimer’s Disease: Focus on Agitation and Aggression. A Report From the Eu/Us/Ctad Task Force

Abstract: Background: The management of neuropsychiatric symptoms (NPS) such as agitation and aggression is a major priority in caring for people with Alzheimer’s disease (AD). Agitation and aggression (A/A) are among the most disruptive symptoms, and given their impact, they are increasingly an important target for development of effective treatments. Considerable progress has been made in the last years with a growing number of randomized controlled trials (RCTs) of drugs for NPS. The limited benefits reported in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Information about MCID is very important for newer scales; less widely used measures, such as the NPI‐C‐A+A; as well as for the novel, IPA criteria‐informed measures. 4 Regarding MCID of NPI‐C‐A+A and NPI‐C‐IPA, follow‐up of 1 month seemed sufficient to detect the group of patients who would be very much improved by 3 months. This finding has important implications for trial design; while symptom response in clinical trials may have a different timeframe than in observational studies such as ours, what is important is that natural variation in symptoms can be observed in a short time frame (1 month) and predicts later response (3 months).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Information about MCID is very important for newer scales; less widely used measures, such as the NPI‐C‐A+A; as well as for the novel, IPA criteria‐informed measures. 4 Regarding MCID of NPI‐C‐A+A and NPI‐C‐IPA, follow‐up of 1 month seemed sufficient to detect the group of patients who would be very much improved by 3 months. This finding has important implications for trial design; while symptom response in clinical trials may have a different timeframe than in observational studies such as ours, what is important is that natural variation in symptoms can be observed in a short time frame (1 month) and predicts later response (3 months).…”
Section: Discussionmentioning
confidence: 97%
“…Although progress has been made in implementing randomized clinical trials (RCTs) for agitation, 3 the choice of optimal outcome measures to demonstrate treatment effectiveness is still unresolved. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the implementation of an interdisciplinary treatment plan defines roles of team members in carrying out assessments and interventions at specified times and helps to move the care plan forward towards the best patient outcome. Further, with clear treatment steps and decision points based on global clinical impression, the clinical team adopts measurement-based care while maximizing efficiency as recommended by guidelines and expert panels (Azermai et al, 2012, Soto et al, 2015. If replicated in larger prospective controlled studies, decreasing the LOS may help to reduce distress to the patients and caregivers and lead to cost savings (Maust et al, 2017).…”
Section: Discussionmentioning
confidence: 99%